What Does the Soul Say?: Metaphysical Uses of Facilitated Communication in the Jewish Ultraorthodox Community - Bilu, Yoram (Ethos, 1997)
Facilitated communication (FC), a set of techniques designed to improve the communication skills of children with pervasive developmental disorders, was transformed in the Jewish ultraorthodox community into a mystical device through which autistic children disclose otherworldly messages. We use this case to study the process whereby, in a given historical moment, specific forms of deviance are selected and molded into ritualized moralistic performances through which the values of the community are reasserted. Following a comparison between clinical and metaphysical FC, we explore synchronic and diachronic aspects of the complex relations between the ultraorthodox and the secular society extrapolated from the case. A comparative analysis of FC sessions and exorcistic rituals of dybbuk possession provides a background for proposing a dichotomous model of mystical pathways to the sacred, highlighting the role of deviants in revitalizing religious beliefs.